En kubansk cigarrlåda - Svensson, Birgitta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
This essay is analyzing why a beautiful Cuban cigar box causes ethnological reflexions on the sensuality of everyday reliquaries as well as issues around health, bitter sweet nostalgia and the capacity of things to give stories a material anchor age. The findings support a conclusion that material objects can create both contemporary insights in changes in society and traces back to the past.